Arc Pair Grammar - Johnson, David E., 1946-; Postal, Paul Martin, 1936- (Book collections on Project MUSE., 1980)
Arc pair grammar is a new, extensively formalized, theory of the grammatical structure of natural languages. As an outgrowth of relational grammar, it constitutes a theoretical alternative to the long-dominant generative transformational approach to linguistics. In this work, David Johnson and Paul Postal offer the first comprehensive presentation of this theoretical framework, which provides entirely new notions of all the basic concepts of grammatical theory: sentence, language, rule, and grammar.Originally published in 1981.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.